Sinergi KPU, BAWASLU, dan DKPP: Pilar Penegakan Demokrasi dalam Pemilu Indonesia - Muhammad Maulana Nazril; Dicky Juliandi; Danii Rizky Mabrury; Surya Sukti (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
General elections (elections) in Indonesia are a major pillar of democracy that require strict supervision and management to ensure fairness and transparency. Independent institutions such as the General Election Commission (KPU), the Election Supervisory Body (BAWASLU), and the Election Organizer Honorary Council (DKPP) play a key role in maintaining election integrity. The KPU is responsible for organizing elections at all levels of government, including planning, implementing, and supervising election stages, with a focus on transparency and public participation. BAWASLU functions as a supervisor to prevent and prosecute election violations, while the DKPP is tasked with handling violations of the election organizer's code of ethics. The research of this paper aims to understand the meaning and main tasks or authorities and functions of each of these institutions. The method used in this study is Library Research and Internet Searching, a literature review of literature in the form of books and articles from relevant internet sources. The results of the analysis show that the synergy between the KPU, BAWASLU, and DKPP is very important in creating democratic and integrity-based elections, with each institution having a role or authority, responsibility, and complementary functions. A deep understanding of the duties and functions of these three institutions is expected to improve the quality of election implementation in Indonesia.